2001
DOI: 10.1159/000050528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Habitual Snoring in a Sample of French Males

Abstract: Background: No data on snoring prevalence obtained with a standard questionnaire exist for France. Major nose-throat abnormalities have been demonstrated in cases with obstructive sleep apnea; evidence of ‘minor’ abnormalities in community studies is scarce. Objectives: The fist objective of our study was to estimate the prevalence of habitual snoring in a sample of middle-aged active males in France. The second objective was to test the hypothesis that ‘minor’ nose-throat abnormalities could be associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
1
10
0
2
Order By: Relevance
“…Bir başka çalışmada ise habituel horlama ile gece burun tıkanıklığı semptomu ve yumuşak damakta sarkma tespit edilmesi ilişkili bulunmuştur. 18 Burundan solunumun güçleşmesi ağızdan solunuma yol açmaktadır. Bazı yazarlar ağızdan solunumun, ÜSY'de daha yüksek bir dirence yol açtığını ve bunun da uyku apne sendromuna katkıda bulunabileceğini bildirmektedir.…”
Section: Discussionunclassified
“…Bir başka çalışmada ise habituel horlama ile gece burun tıkanıklığı semptomu ve yumuşak damakta sarkma tespit edilmesi ilişkili bulunmuştur. 18 Burundan solunumun güçleşmesi ağızdan solunuma yol açmaktadır. Bazı yazarlar ağızdan solunumun, ÜSY'de daha yüksek bir dirence yol açtığını ve bunun da uyku apne sendromuna katkıda bulunabileceğini bildirmektedir.…”
Section: Discussionunclassified
“…The prevalence of habitual snoring in middle-aged French males was reported to be 32%. Age, neck circumference, tobacco consumption, weight excess and large soft palate were independently associated with snoring [16]. Resta et al [17] investigated the prevalence of snoring and OSA in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Teculescu et al (12) reported that the prevalence of habitual snoring in middle aged (23-63 years) French males was 32%. They confirmed that age, excess weight, tobacco smoking, blocked nose at night and large soft palate tissue are independently associated with snoring.…”
Section: Discussionmentioning
confidence: 99%